2016
DOI: 10.4103/ayu.ayu_182_15
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant activity of Rhizophora mucronata leaves (Indian sundarban mangrove): An in vitro and in vivo study

Abstract: Background:Rhizophora mucronata is a salt-tolerant true mangrove which is widely distributed in Indian mangrove forest and traditionally used to treat diabetes and other health ailments.Aim:The aim of this study is to elucidate the role of Indian variety of R. mucronata leaves on glucose impairing metabolism during diabetes by in vitro and in vivo methods.Materials and Methods:The ethanolic fraction of R. mucronata leaves extract (RHE) was assessed for DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…Nowadays, contemporary science might quibble these afore-mentioned traditional uses since their pharmaceutical effects, toxicity, efficacy and safety have not been fully unravelled yet. Only few studies have reported its biological activities, namely antioxidant, anti-inflammatory [7], antimicrobial [8], anti-diabetic [9,10] and anti-viral [11]. For example, Banerjee et al revealed that the methanolic leaves and root extracts are important sources of antioxidant compounds [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, contemporary science might quibble these afore-mentioned traditional uses since their pharmaceutical effects, toxicity, efficacy and safety have not been fully unravelled yet. Only few studies have reported its biological activities, namely antioxidant, anti-inflammatory [7], antimicrobial [8], anti-diabetic [9,10] and anti-viral [11]. For example, Banerjee et al revealed that the methanolic leaves and root extracts are important sources of antioxidant compounds [12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the current study further demonstrates that lipid and lipoprotein irregularities were opposed by the plant extracts in diabetic rats. The hypolipidemic effects of R. mucronata might be due to the impact of its diverse bioactive components, and other consitituents [ 37 ] or the downregulation of LDL epitopes and prevention of 3-hydroxy 3-methylglutaryl coenzyme A reductase [ 38 ]. Indeed, low doses of A. marina had been used as anti-cholesterolemic agents due to its contents in bioactive constituents that might have an antioxidants-like effect, scavenger free radical, and enhance lipid profile and organ function [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many research works and investigations have had been spotted the light on the phytochemical properties of R. mucronata leaves principally, phenolics, flavonoids, and quercetin which have antioxidative, antidiabetic, and cardioprotective activities. Promising antioxidant properties of R. mucronata was induced by inhibiting 1,1-diphenyl-2-picrylhydrazyl (DPPH) and radical scavenging that might be due to the high amount of quercetin ( 31 ).…”
Section: Discussionmentioning
confidence: 99%